CO2 Capture in Ionic Liquids: A Review of Solubilities and Experimental Methods - Elena Torralba-Calleja; James Skinner; David Gutiérrez-Tauste (Journal of Chemistry)
The growing concern of climate change and global warming has in turn given rise to a thriving research field dedicated to finding solutions. One particular area which has received considerable attention is the lowering of carbon dioxide emissions from large-scale sources, that is, fossil fuel power. This paper focuses on ionic liquids being used as novel media for CO2 capture. In particular, solubility data and experimental techniques are used at a laboratory scale. Cited CO2 absorption data for imidazolium-, pyrrolidinium-, pyridinium-, quaternary-ammonium-, and tetra-alkyl-phosphonium-based ionic liquids is reviewed, expressed as mole fractions (X) of CO2 to ionic liquid. The following experimental techniques are featured: gravimetric analysis, the pressure drop method, and the view-cell method.